2017
DOI: 10.1038/s41550-017-0237-7
|View full text |Cite
|
Sign up to set email alerts
|

Protostellar and cometary detections of organohalogens

Abstract: Organohalogens, a class of molecules that contain at least one halogen atom bonded to carbon, are abundant on Earth where they are mainly produced through industrial and biological processes [1]. Consequently, they have been proposed as biomarkers in the search for life on exoplanets [2]. Simple halogen hydrides have been detected in interstellar sources and in comets, but the presence and possible incorporation of more complex halogen-containing molecules such as organohalogens into planet-forming regions is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 33 publications
1
83
0
Order By: Relevance
“…Moreover, we have not detected any other halogen-bearing neutral at concentrations that can explain the observed increase in the halogen-to-oxygen ratio with distance (see also Le Roy et al 2015). The presence of organohalogens in 67P has been reported recently by Fayolle et al (2017), but in insufficient amounts to be able to contribute significantly. Therefore, the source cannot be a secondary source, so it has to be a distributed source (Cottin & Fray 2008): its origin lies in the sublimation of HF and HCl from icy dust.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, we have not detected any other halogen-bearing neutral at concentrations that can explain the observed increase in the halogen-to-oxygen ratio with distance (see also Le Roy et al 2015). The presence of organohalogens in 67P has been reported recently by Fayolle et al (2017), but in insufficient amounts to be able to contribute significantly. Therefore, the source cannot be a secondary source, so it has to be a distributed source (Cottin & Fray 2008): its origin lies in the sublimation of HF and HCl from icy dust.…”
Section: Discussionmentioning
confidence: 82%
“…As a few examples, Belloche et al (2014) reported the first detection of a branched carbon-chain molecule in the ISM, isopropyl cyanide (C H CN 3 7 ), in band3 observations of Sgr B2. Later, McGuire et al (2017) detected methoxymethanol (CH 3 OCH 2 OH) in surprisingly high abundance toward NGC 6334I in bands 6and7 observations, while Fayolle et al (2017) identified methyl chloride (CH 3 Cl) for the first time using band7 observations of IRAS 16293-2422. These observations, among many others, demonstrate the power of ALMA for studies of our molecular universe in the 1-3mm wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…There are several pathways to destroy HCl through photodissociation, photoionization, or reactions with He + , H + 3 , and C + . Methyl chloride, CH 3 Cl, was also recently identified in the young stellar object IRAS 16293 − 2422 and the gaseous coma of comet 67P/Churyumov-Gerasimenko (Fayolle et al, 2017), suggesting that chlorine chemistry in space also extends to more complex species (see, e.g., Acharyya & Herbst, 2017 for gas-grain chemical models of chlorine chemistry).…”
Section: Introductionmentioning
confidence: 94%